Perception of people toward life insurance policy - Varsha Virani (Journal of Management and Science, 2022)
Insurance companies play an important role in the welfare of human well-being by providing protection to millions of people against life risks such as uncertain death or accident. Even the life insurance is fastest growing service sector in India after privatization and increase in FDI. Thus it has become essential to study the buying pattern of the life insurance policies. The current study examines the various factors that affect the consumer perception towards life insurance policy. Data was collected with the help of structured questionnaire. The sample constituted of 100 respondents from Rajkot city, Gujarat. The statistical technique used for the analysis is descriptive and graphical.